Cytokines, Chemokines, and Other Biomarkers of Response for Checkpoint Inhibitor Therapy in Skin Cancer - Bridge, Jennifer A.; Lee, James C.; Daud, Adil; Wells, James W.; Bluestone, Jeffrey A. (Frontiers in Medicine, 2018)
Immunotherapy for skin malignancies has ushered in a new era for cancer treatments by demonstrating unprecedented durable responses in the setting of metastatic Melanoma. Consequently, checkpoint inhibitors are now the first-line treatment of metastatic melanoma and widely used as adjuvant therapy for stage III disease. With the observation that higher tumor mutational burden correlates with a better response, checkpoint inhibitors are tested in other skin cancer types of known high tumor mutational burden with promising results and recently became the first-ever FDA-approved treatment for metastatic Merkel cell carcinoma. The emerging new standards-of-care will necessitate more precise biomarkers and predictors for treatment response and immune-related adverse events. Measurable immune-related mediators are currently under investigation as factors that promote or block the response to cancer immunotherapy and may provide insights into the underlying immune response to the tumor. Cytokines and chemokines are such mediators and are crucial for facilitating the recruitment and activation of specific subsets of leukocytes within the microenvironment of skin cancers. The exact mechanisms of how these meditators, both immunological and non-immunological, operate in the tumor microenvironment is an area of active research, so to reliable biomarkers of responses to cancer immunotherapy. Here, we will review and summarize the expanding body of literature for immune-related biomarkers pertaining to Melanoma, Basal cell carcinoma, Squamous cell carcinoma, and Merkel cell carcinoma, highlighting clinically relevant checkpoint inhibitor therapy biomarker advancements.